A bibliometric analysis of budgetary slack: Insights from web of science and China National Knowledge Infrastructure using CiteSpace - Chenfei Zhuang; Norhayati Binti Alias; Noraizah Binti Abu Bakar (Sustainable Futures)
Purpose: This study conducts a comprehensive bibliometric analysis to explore the evolution and current status of research on budgetary slack, aiming to identify development trends and suggest future directions in this important field of budgeting. Design/Methodology/Approach: The research employs bibliometric methods using CiteSpace software to analyze publication data from both the Web of Science (WoS) and China National Knowledge Infrastructure (CNKI), enabling cross-comparison between international and Chinese research. Findings: The results indicate that (1) WoS publications on budgetary slack have generally increased over time, while CNKI research started later and has declined since 2012. This decline may reflect Chinese scholars' shift toward publishing on international platforms rather than a reduced focus on the topic. (2) Leading institutions in WoS are primarily based in the United States and exhibit closer collaboration, while research in CNKI is more fragmented, with weaker clustering effects. (3) Both databases investigate the influencing factors of budgetary slack, though the specific research emphases differ. Research implications: This analysis identifies research gaps and potential collaboration opportunities between international and Chinese scholars, offering insights for future research directions.. Originality/Value: This study systematically compares international and Chinese research on budgetary slack using bibliometric methods. It provides a foundation for uncovering research hotspots, collaboration patterns, and theoretical frameworks across different academic environments, thereby contributing to the integration of global research in this field.